The EU directive on road infrastructure safety management - Research at the national and European levels - Macedo, A. L. (2010)
In November 2008 the European Parliament and the Council have adopted the Directive 2008/96/EC aiming at the improvement of road infrastructures safety management in the Trans-European Road Network, by setting up appropriate procedures which can be extended to national networks, namely through the application of guidelines by the Member States. Research and dissemination of research results play an important part in this process. At the Transportation Department of the National Laboratory for Civil Engineering (LNEC), in Portugal, a special attention has been given, over the time, to road infrastructure safety issues, either in the scope of European projects in this area or through studies within collaboration agreements with road and traffic administrations. Based upon this experience, in this article a concise description is made of the main aspects of the EU Directive and on related research studies, which provided sound scientific and technical basis for the proposed procedures, thus contributing to the overall objective of a continuous and widespread improvement of road safety.